GEJALA DEPRESI PADA REMAJA DI SEKOLAH MENENGAH ATAS - Desi, Desi; Felita, Aris; Kinasih, Angkit (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Depression is a mental disorder that is common in the world. Depression can cause difficulty concentrating, affecting once social functioning, and adjusting difficulty, and can even lead to suicidal behavior for individuals who have severe depression. Adolescence is a period of development, and during this period, adolescents often experience a period of identity and ambiguous crisis. This crisis identity causes adolescents to become unstable, aggressive, the conflict between attitudes and behavior, emotional and sensitive shakiness, too fast, and rash to take extreme actions. The purpose of this study was to identify depressive symptoms in adolescents in high school. Quantitative research with this survey approach involves students from SMA NEGRI 1 SALATIGA who were chosen randomly (random sampling). Determination of sample size using the Slovin formula with an error tolerance of 0.05. A total of 175 participants consisted of grades 10 and 11, consisting of 75 male students and 100 female students. The results of the study showed that 24% of male students were identified with symptoms of depression while females, there were as many as 40% identified as depressive symptoms. The limitation of this study is that it only uses one variable, showing the percentage of depressive symptoms in early adolescents.